Intersectionality and the invisibility of transgender health in the Philippines - Luis Emmanuel A. Abesamis (BMC, 2022)
Abstract Transgender (trans) Filipinos are disproportionately vulnerable to health problems because of the inaccessibility of essential healthcare services resulting from the invisibility and exclusion of trans health in Philippine health and related social institutions. Because of the institutional prejudice and discrimination against trans Filipinos in Philippine society, an intersectional approach presents an opportunity to analyze the invisibility and potentially elucidate the unique health needs of trans Filipinos. This article elucidates how the invisibility of trans Filipinos in health is a product of co-existing and interacting prejudiced and discriminatory institutions, such as the law, education, and medicine, where the historical experiences of colonization, the hegemony of cisgenderism, and the impact of capitalism remain salient. By elucidating these co-existing and interacting structures and forces, this article highlights the gaps in the Philippine healthcare system, such as the lack of affirming and protective policies for trans health and the limited cultural competence of healthcare providers. In light of these, future research and policy work must work towards integrating gender-specific and gender-inclusive approaches, centering the voices of trans Filipinos in health discourses, and decolonizing and expanding the local understanding of trans health among Filipinos.